1996
DOI: 10.1177/106939719603000102
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Jealousy: Evolution or Social Construction?

Abstract: Buss, Larsen, Westen, and Semmelroth claimed that sex differences in the dislike of sexual or emotional infidelity supported the socio-biological hypothesis of men (i.e., most men) having evolved sexual jealousy, whereas women (i.e., most women) evolved emotional jealousy. In two studies with 745 undergraduates, our finding was that, similar to the Buss et al. finding, over 50% of the men and women reported greater upset over imagined emotional infidelity. Subjects responded to a self-rating of jealousy, the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 10 publications
1
20
0
8
Order By: Relevance
“…These findings have been replicated extensively in the U.S. using hypothetical scenarios (Brase et al 2004;Buunk et al 1996;Hupka and Bank 1996;Levy and Kelly 2010;Murphy et al 2006;Shackelford et al 2002). In a meta-analysis based on 72 samples, including both college-age and adult samples and unpublished studies, Hofhansl et al (2004) reported a moderate effect size of .64 for overall gender differences.…”
Section: Hypothetical Reactions To Infidelitymentioning
confidence: 71%
See 1 more Smart Citation
“…These findings have been replicated extensively in the U.S. using hypothetical scenarios (Brase et al 2004;Buunk et al 1996;Hupka and Bank 1996;Levy and Kelly 2010;Murphy et al 2006;Shackelford et al 2002). In a meta-analysis based on 72 samples, including both college-age and adult samples and unpublished studies, Hofhansl et al (2004) reported a moderate effect size of .64 for overall gender differences.…”
Section: Hypothetical Reactions To Infidelitymentioning
confidence: 71%
“…Since that time, debate has focused largely on the existence of these possible gender differences, disputing questions of theoretical soundness (e.g. Buss et al 1996;DeSteno and Salovey 1996;Harris and Christenfeld 1996;Hupka and Bank 1996) and study methodology (e.g. DeSteno et al 2002;Hofhansl et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional infidelity occurs when one's partner channels resources such as romantic love, time, and attention to someone else. Researchers working from other theoretical perspectives, including social role theory and socialisation-based models, also have documented these sex differences in emotional reactions to infidelity (e.g., DeSteno & Salovey, 1996;Hupka & Bank, 1996).…”
Section: ó 2000 Psychology Press Ltdmentioning
confidence: 99%
“…Desde una perspectiva cultural (DeSteno y Salovey, 1996;DeSteno, Bartlett, Braverman y Salovey, 2002;DeSteno, Valdesolo, y Bartlett, 2006); Harris, 2000;2003a;2003b;Harris y Christenfeld, 1996a;1996b;Hupka, 1981;Hupka y Bank, 1996) se han ofrecido explicaciones alternativas que sitúan el origen de tales diferencias entre hombres y mujeres en el proceso de socialización diferencial y en la influencia social y cultural. Las diferencias entre hombres y mujeres serían explicables desde las diferentes adscripciones de unos y otros a las normas y roles de género dominantes en un contexto ideológico determinado.…”
Section: This Present Study Explores the Differences Between Women's unclassified